2017
DOI: 10.1017/jfm.2017.96
|View full text |Cite
|
Sign up to set email alerts
|

Droplets in turbulence: a new perspective

Abstract: Stirring olive oil and vinegar to make salad dressing creates an emulsion of vinegar droplets in oil. More vigorous stirring gives smaller droplets, while if left to sit the droplets will begin to coalesce and the two fluids will separate. In this vein, Dodd & Ferrante (J. Fluid Mech., vol. 806, 2016, pp. 356-412) present a new analysis of how homogeneous turbulence in a carrier fluid interacts with a suspension of droplets of an immiscible liquid. Based on a set of direct numerical simulations, the authors p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Interface-capturing simulations of homogenous isotropic turbulence (Dodd and Ferrante, 2016;Perlekar et al, 2012;Komrakova et al, 2015;Bolotnov, 2013) and shear flows (De Vita et al, 2019; have shed some light on the effect of coalescence on turbulence. Notably, Dodd and Ferrante (2016) and Maxey (2017) showed that coalescence is a source of turbulent kinetic energy, while breakup is a sink. Scarbolo et al (2015) investigated the effect of Weber number on breakup and coalescence, Soligo et al (2019) modeled surfactant laden drops in turbulent channel flows, while Bolotnov et al (2011) used the level-set method to simulate bubbly channel flows.…”
Section: Introductionmentioning
confidence: 99%
“…Interface-capturing simulations of homogenous isotropic turbulence (Dodd and Ferrante, 2016;Perlekar et al, 2012;Komrakova et al, 2015;Bolotnov, 2013) and shear flows (De Vita et al, 2019; have shed some light on the effect of coalescence on turbulence. Notably, Dodd and Ferrante (2016) and Maxey (2017) showed that coalescence is a source of turbulent kinetic energy, while breakup is a sink. Scarbolo et al (2015) investigated the effect of Weber number on breakup and coalescence, Soligo et al (2019) modeled surfactant laden drops in turbulent channel flows, while Bolotnov et al (2011) used the level-set method to simulate bubbly channel flows.…”
Section: Introductionmentioning
confidence: 99%
“…Interface-capturing simulations of homogenous isotropic turbulence (Dodd and Ferrante, 2016;Perlekar et al, 2012;Komrakova, Eskin, and Derksen, 2015;Bolotnov, 2013) and shear flows (De Vita et al, 2019; have shed some light on the effect of coalescence on turbulence. Notably, Dodd and Ferrante (2016) and Maxey (2017) showed that coalescence is a source of turbulent kinetic energy, while breakup is a sink. Scarbolo, Bianco, and Soldati (2015) investigated the effect of Weber number on breakup and coalescence, Soligo, Roccon, and Soldati (2019) modelled surfactant laden drops in a turbulent channel flows, while Bolotnov et al (2011) used the level-set method to simulate bubbly channel flows.…”
Section: Introductionmentioning
confidence: 99%
“…This has led us to question whether the introduction of droplets actually causes the carrier fluid to contain more energy at high wavenumbers. Also, Maxey (2017) suggests providing a closer analysis of the energy spectrum in his review of Dodd & Ferrante (2016). Furthermore, our interest in the droplets’ effect on the energy spectrum is to help improve subgrid-scale models for large-eddy simulation (LES) of multiphase turbulent flows.…”
Section: Introductionmentioning
confidence: 99%